Lessons learned from an evaluation of referrals to the emergency department - Roee Gorodetzer; Evan Avraham Alpert; Zvika Orr; Shifra Unger; Todd Zalut (BMC, 2020)
Abstract Background Emergency department (ED) crowding is an international phenomenon dependent on input, throughput, and output factors. This study aims to determine whether patterns of potentially unnecessary referrals from either primary care physicians (PCPs) or urgent care centers (UCCs) can be identified, thereby to reduce ED visits by patients who could be treated elsewhere. Literature from the United States reports up to 35% unnecessary referrals from UCCs. Methods A retrospective cohort study was conducted of patients referred to an ED in Jerusalem by either their PCP or a group of UCCs with a full range of laboratory tests and basic imaging capabilities between January 2017 and December 2017. The data were analyzed to identify referrals involving diagnoses, specialist consultations, and examinations unavailable in the PCP's office or UCC (e.g., ultrasound, CT, echocardiogram, or stress test); these referrals were considered necessary for completion of the patient work-up. If patients were evaluated by an ED physician and sent home after an examination or laboratory test available at least in the UCC, the referrals were considered potentially unnecessary. Results Significantly more referrals were made by PCPs than UCCs (1712 vs. 280, p < 0.001). Significant differences were observed for orthopedics, general surgery, and obstetrics/gynecology referrals (p = 0.039, p < 0.001, p = 0.003). A higher percentage of patients referred by PCPs had potentially unnecessary visits compared to patients referred by UCCs (13.9% vs. 7.9%, p = 0.005). Conclusion A robust UCC system may help further reduce potentially unnecessary visits (including complex patients) to the ED.